Penentuan Sektor Unggulan di Kabupaten Sijunjung Sebelum dan Sesudah Covid-19 - Ladhisa Safa Moury; Satrianto, Alpon (Universitas Negeri Padang, 2024)
This research aims to see what sectors are included in the basic sectors in Sijunjung Regency before and after Covid-19 according to the Dynamic Location Quotient (DLQ) and Shift-Share methods, and see what sectors are included in the leading sectors in Sijunjung Regency before and after Covid-19 according to a combination of DLQ and Shift-Share methods. The type of research carried out is descriptive research with a quantitative approach. Data sourced from the Central Statistics Agency of West Sumatra Province and Sijunjung Regency before Covid-19 in 2015 - 2019 and after Covid-19 in 2021 - 2023 using the DLQ and Shift-Share methods. Based on the results of research using these two methods, it can be concluded that according to the DLQ method the basic sectors in Sijunjung Regency are in the primary, secondary and tertiary sectors, but are dominated by the tertiary sector. Based on the shift-share method, the base sector is dominated by the secondary and tertiary sectors. Meanwhile, based on a combination of the DLQ and Shift-Share methods before Covid-19, the leading sector in Sijunjung Regency was the tertiary sector. Meanwhile, after Covid-19, the leading sectors in Sijunjung Regency are the secondary and tertiary sectors.